2020
DOI: 10.5696/2156-9614-10.27.200912
|View full text |Cite
|
Sign up to set email alerts
|

Levels of PM 10 and PM 2.5 and Respiratory Health Impacts on School-Going Children in Kenya

Abstract: Background. The respiratory system of children is vulnerable to exposure to particulate matter (PM) with a diameter of less than 2.5 and 10 μm (PM2.5 and PM10) or even lower. Objective. This study assessed PM10 and PM2.5 levels and respiratory health impacts on children in schools located in an industrialized suburb in Kenya. Method. The PM10 and PM2.5 levels were sampled from five public primary schools in Athi River Township and a control school during the wet and dry seasons. Outdoor and classroom samples w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Because PM10 concentration remained normal over the study period, it was not associated with more respiratory hospital visits, even though these particles were linked to a higher risk of admission in settings where PM10 was abnormally high 21,25,26 .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Because PM10 concentration remained normal over the study period, it was not associated with more respiratory hospital visits, even though these particles were linked to a higher risk of admission in settings where PM10 was abnormally high 21,25,26 .…”
Section: Discussionmentioning
confidence: 91%
“…Most studies in Africa explored PM adverse effects on respiratory diseases among children in schools, near industrial areas, or mine dumps. This is the rst study to our knowledge that has assessed the effect on hospital visits 4,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also associated with respiratory health risks among communities living within the dispersion zone of the cement industries. Lower lung function indices and ventilation capacity have been frequently observed in the exposed group in studies focusing on cement dust exposure and respiratory health [11]. In particular, the research that has been done in Athi River Township revealed that the downwind sites had 24-hour mean ambient PM 2.5 and PM 10 levels that were above the WHO ambient air quality guidelines [12].…”
Section: Introductionmentioning
confidence: 99%
“…Pollutants mainly originate from industries, coal power plants, biomass burning, automobiles, and household solid fuel usage. The fine PM fraction with an aerodynamic diameter of less than 2.5 μm (PM 2.5 ) has become a great concern because it can affect visibility, induce changes in the global climate due to its capability to absorb and scatter solar radiation, , and cause serious health effects in the human population. Moreover, PM 2.5 has a damaging effect on human health due to its capability to penetrate deep into the lungs and cardiovascular system. Specifically, this effect gives rise to diseases, including short- and long-term respiratory problems (e.g., coughing, asthma, and lung cancer); increases mortality related to cardiovascular diseases (heart diseases and heart rate variation); ,, causes Alzheimer’s or neurological dementia; and exacerbates the possible airborne transmission of COVID-19, which has caused a global pandemic.…”
Section: Introductionmentioning
confidence: 99%